Chapter La libertas ecclesiae nel tardo medioevo - D'Acunto, Nicolangelo (Firenze University Press, 2025)
The author analyzes apostolic letters, conciliar decrees and canon law to highlight how, compared to the salient phase of monarchical affirmation between the 11th and 13th centuries - during which the libertas Ecclesiae could extend to unprecedented alliances such as the libertas Ytalie supported by the municipalities and was voted to the defense of the patrimonial and juridical interests of local ecclesiastical bodies in the coincidence of their libertas with the libertas Ecclesiae -, in the late Middle Ages pontifical action was concentrated more generally against the peripheral ecclesiastical bodies which, under the pretext of a traditional notion of freedom, escaped the control of the bishops and the Pope who claimed the preservation of ecclesiastical freedom.